Relative nullity space foliation of the screen distribution of a lightlike hypersurfaces. - ATINDOGBE, COMLAN CYRIAQUE; EZIN, JEAN-PIERRE; TOSSA, JOEL (My University, 2006)
This paper deals with results concerning the relative nullity foliation of the screen distribution of a lightlike Einstein hypersurface $M$ in the Lorentzian space $\mathbb{R}^{n+2}_{1}$ and gives a characterization theorem for the relative nullity spaces. Many differences from the Riemannian case are due to the fact that the metric in consideration is degenerate.
Keywords: lightlike Einstein hypersurfaces; relative nullity foliation; screen distribution; index of relative nullity